Application of PLASMIC Score in Risk Prediction of Thrombotic Thrombocytopenic Purpura: Real-World Experience From a Tertiary Medical Center in Taiwan - Lee, Chun-Hui; Huang, Yi-Ching; Li, Sin-Syue; Hsu, Ya-Ting; Chen, Ya-Ping; Chen, Tsai-Yun (Frontiers in Medicine, 2022)
Thrombotic thrombocytopenic purpura (TTP) is a life-threatening disorder caused by severe ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 repeats, member 13) deficiency (activity <10%). Urgent intervention based on the timely evaluation of ADAMTS13 level is crucial to guide optimal therapy. The recently developed PLASMIC score based on seven items allows the rapid identification of patients at high risk for TTP due to severe ADAMTS13 deficiency. This retrospective study included 31 hospitalized patients with suspicious thrombotic microangiopathy in National Cheng Kung University Hospital from December 2016 to July 2021. Data on ADAMTS13 activity and medical and laboratory information were retrieved from medical records. The PLASMIC score could be calculated in 24 of the 31 patients with available data, and the final cohort was stratified according to the 7-point PLASMIC score. All patients with high PLASMIC score (6–7) exhibited severe ADAMTS13 deficiency (activity ≤10%). One patient with a brain tumor and a PLASMIC score of 6 did not have severe ADAMTS13 activity of ≤10%. The patients in the intermediate- and low risk groups (PLASMIC scores of 5 and 0–4, respectively) exhibited ADAMTS13 activities of above 10%. Given the role of prompt diagnosis in the timely delivery of appropriate therapy, these findings confirm and strengthen the predictive value of the PLASMIC score in patients at high risk for TTP due to severe ADAMTS13 deficiency.